An automated analysis of the patient’s condition and assessment of medical sessions (hypoxic therary). - Poliagushko, L. G. (Інститут проблем реєстрації інформації НАН України, 2019)
The task of creating an expert system for conducting an automated assessment of patients' status and analyzing the results of conducting medical sessions is examined. This system is part of an automated software and hardware complex for hypoxic therapy. The paper describes the proposed architecture of the expert system and the interaction of its main modules. The developed formal model of representation of the knowledge base is described. This model is based on product rules. The proposed Knowledge Base representation allows for the presentation of rules with different levels of nesting conditions and consequences, as well as maintaining rules using MySQL. The model is adapted to use the Rete algorithm. The article describes the output mechanism through the «mapping-operation» procedure and the Rete algorithm, which is a quick comparison tool with the template. The created expert system conducts an automated assessment of patients' condition and analysis of diagnostic sessions and course of treatment based on parameters of the respiratory and cardiovascular system of a person. This expert system has improved the effectiveness and safety of procedures for hypoxic therapy, which in the future ensure the use of automated software and hardware for hypoxic therapy, not only in medical centers, but also at home. Also, this system can work with other medical devices or as an independent program for assessing medical procedures and providing medical advice. The main improvements will be to fill the knowledge base with the necessary rules and facts. The paper presents the algorithm's work and the presentation of the rules on the example of the evaluation of the diagnostic session.